Principle Of Information Transparency; Comparative Analysis Of Consumer Protection Laws And Qur'anic Ethics In Al-Baqarah Verse 42 - Makfi, Miqdam; Muhammad, Hasman Zhafiri (Fakultas Hukum Universitas Widya Mataram, 2025)
This study aims to analyze the principle of product information transparency under Law Number 8 of 1999 concerning Consumer Protection (UUPK) and to examine the ethical values of the Qur’an based on the exegesis of QS Al-Baqarah: 42, which contains the prohibitions of taktumūl al-ḥaqq (concealing the truth) and talbīs al-ḥaqq (mixing truth with falsehood). The research employs a normative juridical method using statutory, conceptual, and thematic tafsir approaches. Data sources consist of primary legal materials, including the UUPK, implementing regulations, and Qur’anic exegesis texts; secondary legal materials, such as legal literature, journal articles, and relevant research findings; and tertiary legal materials, including legal dictionaries and encyclopedias. The data were analyzed qualitatively through deductive reasoning. The results reveal that the UUPK normatively affirms the consumer’s right to receive accurate, clear, and truthful information (Article 4 letter c) and the obligation of business actors to provide such information (Article 7 letter b), reinforced by the prohibition of misleading acts in Articles 8–10. From the perspective of Qur’anic ethics, QS Al-Baqarah: 42 advocates honesty, openness, and the avoidance of information distortion, which are highly relevant to consumer protection. The normative integration of positive legal provisions and Qur’anic ethical principles produces a conceptual model of consumer protection based on moral-spiritual values, thereby strengthening the effectiveness of regulations in preventing misleading marketing practices. These findings enrich the study of modern economic law through the synthesis of positive law norms and Qur’anic values in establishing a fair consumer protection regime. Keywords: Information Transparency; Consumer Protection; UUPK; Qur’anic Ethics; QS Al-Baqarah: 42